Effect of ionic strength of the equilibrium solution upon cadmium adsorption in Brazilian Oxisols - Pierangeli, Maria Aparecida Pereira; Guilherme, Luiz Roberto Guimarães; Oliveira, Leyser Rodrigues; Curi, Nilton; Silva, Marx Leandro Naves (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the effects of ionic strength upon Cd adsorption in samples of 17 Brazilian Oxisols. The reaction of the soil samples with 0.167 mmol L-1 Cd(NO3)2 at pH 6.5, using 5, 50 and 150 mmol L-1 Ca(NO3)2 as background solutions for ionic strength of 15, 150 and 450 mmol L-1, respectively (1:100 soil:solution ratio) was evaluated during 72 hours. Increasing ionic strength caused Cd adsorbed to decrease in all soils, with average adsorption values of 12.17, 6.92 and 5.70 mmol kg-1 for ionic strength of 15, 150, and 450 mmol L-1, respectively. In the lowest ionic strength, the adsorbed Cd fraction correlated positively with soil properties such as specific surface area, clay, organic matter, kaolinite and hematite content, ammonium oxalate-, DCB-, and sulfuric acid digestion-Fe, as well as sulfuric acid digestion-Al. For the ionic strength of 150 mmol L-1, there was not correlation between the adsorbed Cd fraction and the attributes of the soils, while in 450 mmol L-1 there was correlation with the organic matter and specific surface area. The Cd is not adsorbed by outer-sphere complex, and is potentiality bioavailable in those Oxisols.
Keywords: soil sorption; chemical contamination; pollutants; trace elements